2021
DOI: 10.1186/s12917-020-02732-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host breeds on gut microbiome and serum metabolome in meat rabbits

Abstract: Background Gut microbial compositional and functional variation can affect health and production performance of farm animals. Analysing metabolites in biological samples provides information on the basic mechanisms that affect the well-being and production traits in farm animals. However, the extent to which host breeds affect the gut microbiome and serum metabolome in meat rabbits is still unknown. In this study, the differences in phylogenetic composition and functional capacities of gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 77 publications
2
21
0
3
Order By: Relevance
“…In our study, some species that are known as SCFAs (e.g. butanoate) producer [Roseburia hominis (32,33), Odoribacter splanchnicus (34), Ruminococcus callidus (35), Lachnospiraceae bacterium 3_1_46FAA (36), Bacteroides uniformis (37) and Butyricimonas synergistica (38)], together with the metabolic pathway of producing butanoate (CENTFERM-PWY and PWY-6590) were enriched in the healthy controls. Importantly, both of the two pathways had significantly positive correlations with the above bacterials.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, some species that are known as SCFAs (e.g. butanoate) producer [Roseburia hominis (32,33), Odoribacter splanchnicus (34), Ruminococcus callidus (35), Lachnospiraceae bacterium 3_1_46FAA (36), Bacteroides uniformis (37) and Butyricimonas synergistica (38)], together with the metabolic pathway of producing butanoate (CENTFERM-PWY and PWY-6590) were enriched in the healthy controls. Importantly, both of the two pathways had significantly positive correlations with the above bacterials.…”
Section: Discussionmentioning
confidence: 67%
“…Alloprevotella can produce moderate amounts of acetate and succinate and decrease lifetime cardiovascular disease risk ( Downes et al, 2013 ; Ricaboni et al, 2016 ; Xin et al, 2019 ). Some genera such as Coprococcus and Ruminiclostridium have been demonstrated to produce short-chain fatty acids, which is beneficial to regulate energy intake and maintain the morphology and function of intestine and intestinal epithelial cells ( Tan et al, 2014 ; Ye et al, 2021 ). Moreover, Ruminiclostridium , as an intestinal beneficial bacterium, is involved in the positive regulation of the growth performance and decrease of gastrointestinal diseases of animals ( Tan et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that the relative contribution to GH5_1 of R. albus reaches 72.11% and only R. callidus contains GH48 family in all potential bacterial biomarkers of H_NDF group. R. callidus is a producer of short-chain fatty acids (SCFAs), which can be used as a bacterial biomarker for improving the health and production performance of meat rabbits ( Ye et al, 2021 ). S. bovis is a kind of separable bacteria existing in the rumen contents of yak, which can utilize cellobiose, arabinose, mannose, glucose, etc.…”
Section: Discussionmentioning
confidence: 99%